Resolution of a Five-Component Mixture of Quaternary Ammonium Surfactants on Silica Gel 60 F254 High Performance Thin Layer Chromatographic Plates - Bhawani, Showkat Ahmad; Othman, Bin Sulaiman; Ziya, Ahmad Khan; Rokiah, Binti Hashim; Mohamad Nasir, Bin Mohamad Ibrahim (American Oil Chemists' Society, 2011)
The mutual separation of a mixture of cetyltrimethyl ammonium chloride (CTAC), methyl trioctyl ammonium bromide (MTOB), dodecyltrimethyl ammonium chloride (DTAC), benzyltrimethyl ammonium chloride (BTAC) and tetrabutyl ammonium bromide (TBAB), was achieved on silica high performance thin layer chromatographic plates using dimethyl sulfoxide with aqueous sodium-L-tartrate dibasic dihydrate as the solvent system. The effect of concentration of sodium-L-tartrate dibasic dihydrate on the mobility of all the five quaternaries was examined. The limit of detection of CTAC, MTOB, DTAC, BTAC and TBAB was estimated as 0.6, 0.6, 0.3, 0.6 and 0.3 lg/zone, respectively. The method developed was utilized to identify these surfactants in different spiked water samples after their preliminary separation.